Acceleration profiles in elite Australian soccer - Varley, M. C.; Aughey, R. J. (International Journal of Sports Medicine, 2013)
We quantified the acceleration and high-velocity running of elite Australian soccer players. We hypothesised that high-intensity activity would be underestimated when excluding acceleration during match analysis given its high metabolic demand and occurrence at low velocities. Player movements were observed from 29 players (forwards and central and wide defenders and midfielders) during domestic Australian competition using 5-Hz global positioning system. Effort occurrence were determined for high-velocity running, sprinting and maximal accelerations. The commencement and final velocity of maximal accelerations were also identified. Players undertook an 8~fold greater number of maximal accelerations than sprints per game (65±21 vs. 8±5). Of maximal accelerations ~98% commenced from a starting velocity lower than what would be considered high-velocity running while ~85% did not cross the high-velocity running threshold. The number of efforts performed in all categories were position dependent (P<0.001). Wide defenders performed more maximal accelerations (P<0.006) and central defenders and midfielders performed less sprints compared to all other positions (P<0.02). Maximal accelerations are frequently undertaken during a match often occurring at low velocities. Excluding maximal accelerations in match analysis research may underestimate the amount of high-intensity movements undertaken. Additionally positional differences in high-intensity movements should be accounted for when developing specific conditioning drills.